PERENCANAAN SISTEM OPERASIONAL ANGKUTAN WISATA DI KOTA DENPASAR - Dyah Ayu Lesatri; P. Alit Suthanaya; D.M. Priyantha Wedagama (JURNAL SPEKTRAN, 2017)
Abstract: Tourism is the main sector for the economy of Bali. Denpasar City as the capital city of Bali Province is expected to maintain its position as one of main tourist destinations by increasing and improving existing tourism facilities, and one of them with the provision of tourism transport that serving tourists heading into tourism attraction in the city of Denpasar. The purposes of this research are to analyze the potential demand, tourism transport route and the characteristic of operational system of tourism transport in Denpasar City. From the analysis that has been done, it is obtained that the potential demand of tourist transport in Denpasar City is 438.576 people in 2013 and it is estimated to be 485.998 in 2017. The highest number of tourist those visit the attraction places through the routes of : Belanjong Pillar, Serangan Island, Central Management of Mangrove Forest, The Village of Budaya Kertalangu, Taman Budaya Art Centre, Museum Painting Fingerprint, Bajra Sandhi Monument, Kumbasari Market, Badung Market, Bali Museum.  Alternatives tour packages include regular tour packages with 10 attractions, regular city tours, regular nature tours, city tour charters, and natural attraction charters. Tourist transports operate using medium buses and minibus for 8 hours service time from 09.00 am until 17.00 pm for regular and 4,5 hours until 5,5 hours for charter package. The headway is set 30 minutes.